2010
DOI: 10.1021/jp105029m
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach for Preparing Transparent Conductive Graphene Films Using the Controlled Chemical Reduction of Exfoliated Graphene Oxide in an Aqueous Suspension

Abstract: We report a simple method for preparing transparent conductive graphene films using a chemically converted graphene (CCG) suspension that was obtained via controlled chemical reduction of exfoliated graphene oxide (GO) in the absence of dispersants. Upon thermal annealing of the CCG films, the films displayed a sheet resistance on the order of 103 Ω·◻−1 at 80% transparency (550 nm), with a bulk conductivity on the order of 102 S·cm−1. FT-IR, UV−visible, and X-ray photoelectron spectroscopy results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 45 publications
2
76
0
Order By: Relevance
“…The graphitization temperature of carbon materials is known to be 1100˚C [13], at which the residual oxygen functional groups in RGO will be completely eliminated [50], contributing to the improvement of electrical conductivity. From the linear I-V curves the conductivity of GO, RGO and RGO-1100˚C was estimated to be 4.2 × 10 −4 , 24 and 210 S/cm, corresponding to GO, RGO and RGO-1100˚C, respectively, which is comparable to that presented by Geng et al [51]. The I-V measurement data, in conjunction with XPS and Raman results, reveal that the conductivity of GO increased with increasing sp 2 carbon content and with increasing I D /I G .…”
Section: Electrical Propertysupporting
confidence: 85%
“…The graphitization temperature of carbon materials is known to be 1100˚C [13], at which the residual oxygen functional groups in RGO will be completely eliminated [50], contributing to the improvement of electrical conductivity. From the linear I-V curves the conductivity of GO, RGO and RGO-1100˚C was estimated to be 4.2 × 10 −4 , 24 and 210 S/cm, corresponding to GO, RGO and RGO-1100˚C, respectively, which is comparable to that presented by Geng et al [51]. The I-V measurement data, in conjunction with XPS and Raman results, reveal that the conductivity of GO increased with increasing sp 2 carbon content and with increasing I D /I G .…”
Section: Electrical Propertysupporting
confidence: 85%
“…12 In the absorption spectrum of the wrinkle-like graphene sheets (Figure 1c), a characteristic sp 2 absorption peak is located at approximately 280 nm. 21 Another peak is discernible at 840 nm, 22 unlike the planar graphene sheet ( Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that interlayer distance in CCG-A800 films is reduced to 0.354 nm, approaching the value of bulk graphite. The transparency reduced from this point, while the R s was reduced linearly to the order of 10 3 Ω sq −1 , demonstrating that reduction impacted successfully and uniformly from the outermost to the inner layers [51]. The short circuit current density, overall power conversion efficiency (n), and sheet resistance R SR for devices 1 and 3, respectively, as a function of the number of bending cycles.…”
Section: Thermally Annealing Rgo Transparent Conductive Electrodesmentioning
confidence: 87%
“…In another study, Geng et al reported a simple method for preparing graphene TCEs using seriatim a chemical and a thermal reduction method [51]. More specifically, a converted graphene (CCG) suspension obtained via controlled chemical reduction of exfoliated GO in the absence of dispersants was used as the pristine material and then, upon thermal annealing for 15 min at three different temperatures (200, 400, and 800°C) under vacuum in a furnace tube, the sp 2 carbon networks of the graphene sheets were recovered, with the resulting CCG films exhibiting an R s of the order of 103 Ω sq −1 at 50% transparency (at 550 nm).…”
Section: Thermally Annealing Rgo Transparent Conductive Electrodesmentioning
confidence: 99%